Delayed surgical repositioning of severely intruded permanent maxillary central incisor with completely formed root: A case report with narrative review and a decision/intervention flowchart based on the International Association of Dental Traumatology guidelines - Boris Saha; Sharique Alam; Surendra Kumar Mishra; Md Kalim Ansari (Wolters Kluwer Medknow Publications, 2020)
Intrusive luxation is a severe dental injury and may result in complicated healing sequelae. Management and prognosis of these injuries depend on the factors such as severity of intrusion, stage of root development, and time elapsed between injury and treatment intervention. The aim of this article is to report the management of severe intrusion injury in an adult patient with mature apices who had delayed seeking treatment by 7 days. Three-year follow-up of the patient has shown successful radiographic and clinical outcomes in spite of limiting prognostic factors. This article also reviews the literature regarding current treatment protocols and summarizes the management strategy employed in the present case in a decision/intervention flowchart.